A Depletion‐Free, Ionic, Self‐Assembled Recombination Layer for Tandem Polymer Solar Cells. Issue 5 (11th October 2013) - Lee, Jinho; Kang, Hongkyu; Kong, Jaemin; Lee, Kwanghee
<x xml:space="preserve">Abstract</x> An innovative method for achieving depletion‐free recombination layers (RLs) in inverted tandem polymer solar cells is demonstrated using ionic self‐assembly of a cationic non‐conjugated polyelectrolyte and an anionic metallic polymer. These RLs form tunnel junctions with different work functions of 5.1 eV and 3.9 eV on each of their surfaces. The tandem solar cells containing these RLs exhibit solar power conversion efficiencies exceeding 8.3%. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>